Perancangan Turbin Air Cross-Flow dengan Efisiensi Maksimum untuk Pembangkit Listrik Tenaga Mikro Hidro (PLTMH) di Desa Bungan Jaya Kecamatan Putusibau Selatan Kabupaten Kapuas Hulu Provinsi Kalimantan Barat - Syarif Ishak Alkadri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2018)
To increase electricity access rate of the population in West Kalimantan Province needs to be done a variety of efforts in relation to supply of the electrical energy. One is through the “Pembangkit Listrik Tenaga Mikro Hidro (PLTMH)” as an alternative to reduce the use of “Pembangkit Listrik Tenaga Diesel (PLTD)” which requires a very large operating costs and are not environmentally friendly because it causes air pollution. PLTMH is able to generate electrical energy with environmentally friendly, and can reach the more remote or rural areas. The tools used to generate electricity using micro hydro power is cross-flow water turbine with main component is the turbine wheel (runner) and water spray (nozzle). To design a cross-flow water turbine in order to generate maximum efficiency, it is necessary to consider various design parameters such as angle of the water jet into the runner (angle attack), entry angle of the blade, the ratio of the inside diameter and outside diameter of the blade, as well as the number of blades. This study examines the value of these parameters in designing cross-flow water turbine construction has 27 meters head and water debit is 0.157 m3 in PLTMH Desa Bungan Jaya, Kecamatan Putusibau Selatan, Kabupaten Kapuas Hulu, West Kalimantan Province. The study found that in these locations can be designed cross-flow water turbines with a power of 37 kW and a maximum efficiency of 95%. In order to achieve this efficiency, the turbine is designed to transmit water inlet runner angle or angle attack of 22 °, the angle of the blade entered by 39 °, the ratio of inner diameter and outer diameter runner at 0.60, and the number of blades as much as 18 blade.